Inkling of Innovation Abstract Writing towards Zero Circumvention - Ismail, Norhafizah; Sarji, Nazid; Abd Wahab, Mohd Helmy (Multidisciplinary Applied Research and Innovation, 2023)
Innovation abstract writing skill is crucial to generate innovative publication in any education realm. Circumvention is essence to have care regarding copyright infringement specifically for subject matter expert. The lack of right skill, experience and exposure to write innovation abstract writing adds more troublesome. This study is to analyse the vital element of abstract innovation writing as preliminary part in an article. Next objectives are to compare the element of innovation abstract and research abstract particularly for novice writers and to determine the challenges of innovation development towards high impact value, product sustainability, and zero circumvention.With adoption of Agile software development as methodologies, this innovation determines the challenges of innovation development towards high impact value, product sustainability and zero circumvention. With deployment of Bring Your Own Device (BYOD) conception via KelasLive and YouTube platform, the technique of abstract writing using Curation Mind Mapping (CUMAPP) has been implemented to yield innovation and research abstract from idea to truly existing. Data is collected through 110 participants in webinar of Cam Inilah Nak Tulis Artikel (CINTA) in July 2020 among Malaysian Polytechnic and Community Colleges (PolyCC) during pandemic of COVID-19. The findings conceded innovation abstract writing is pertinent with deep grasping of components namely statement of problem, objectives, theories, methodology, cost of development and potential of commercialization in the writing. Agile is applicable to allow teams with greater quality for change response. In future, it is remarkable for the writers to suggest the product collaborators and enrichment program for product sustainability in a full innovation article to yield more impact to the writing and publication accomplishment.